Apply pressure-strain loop to quantify myocardial work in pulmonary hypertension: A prospective cohort study - Wang, Jian; Ni, Chao; Yang, Menghui; Zhang, Xueming; Ruan, Binqian; Sun, Lingyue; Shen, Xuedong; Shen, Jieyan (Frontiers in Cardiovascular Medicine, 2022)
Objectives: Pressure-strain loop (PSL) is a novel method to quantify myocardial work in many cardiovascular diseases. To investigate the value of myocardial work parameters derived from PSL for evaluating cardiac function and clinical prognosis in patients with pulmonary hypertension (PH). Methods: A total of 52 patients with PH and 27 controls were enrolled in this prospective study. PSLs by echocardiography were used to calculate global work index (GWI) of left ventricle (LV) and right ventricle (RV). Global constructive work (GCW) comprised the sum of myocardial work performed during shortening in systole and during lengthening in isovolumic relaxation. Global wasted work (GWW) comprised the sum of myocardial work performed during lengthening in systole and during shortening in isovolumic relaxation. Global work efficiency (GWE) was defined as GCW/(GCW+GWW). Results: LVGWW, RVGWI, RVGCW and RVGWW were higher in patients than controls (all P<0.001). LVGWE, LVGWI, LVGCW, and RVGWE were lower in patients than controls (all P<0.01). Myocardial work parameters correlated well with clinical and other conventional echocardiographic assessments (all P<0.05). In binary logistic regression analysis, combination of RVGWE and estimation of pulmonary arterial systolic pressure(ePASP) was the best model of clinical outcomes(OR=0.803, P=0.002 and OR=1.052, P=0.015, respectively). Receiver operating characteristic curve demonstrated combination of RVGWE and ePASP was the best predictor of adverse events with 100% sensitivity and 76.3% specificity (AUC=0.910, P<0.001). Conclusions: Myocardial work parameters derived from PSL are emerging markers of cardiac function status and combination of RVGWE and ePASP is a useful predictor of clinical outcome in PH patients.